Experimental Study on Thermal Performance of Semi-transparent PV Window in Winter in Hong Kong. (May 2017) - Wang, Meng; Peng, Jinqing; Li, Nianping; Lu, Lin; Yang, Hongxing
Abstract: Semi-transparent PV (STPV) windows can provide daylight illuminance and electricity generation simultaneously. The performance of semi-transparent PV in saving cooling energy has been proved in previous studies. This study presents the heating performance of STPV window in winter in Hong Kong. The passive heating effect of STPV was investigated experimentally. The results indicated that space heating is not needed for the room equipped with STPV in work time on sunny days. The SHGC and U-value of the STPV were also calculated. The average values of SHGC and U-value are 0.2 and 5.58 W/(m 2 K), respectively.